A spatially-reduced dynamic model for the thermal characterisation of Li-ion battery cells. (19th June 2012) - Muratori, Matteo; Canova, Marcello; Guezennec, Yann
Li-ion electrochemical batteries have become the standard for energy storage in transportation and several studies have related the performance and aging behaviour to the cell temperature during utilisation. This paper proposes a methodology to predict the thermal behaviour of Li-ion battery cells through a spatially-reduced model. An electro-thermal model was formulated to predict the dynamics of the cell voltage, state of charge and internal temperature distribution in relation with the current demand and cooling conditions, applying an analytical solution technique. The model calibration was experimentally conducted and validation results are presented to support the proposed modelling approach.